(untitled) (Equilibrium: Jurnal Pendidikan, 2022)
The coronavirus pandemic made it practically impossible for physical classes to take place in 2020 but thanks to virtual classes which came to our rescue. This study investigated the challenges of virtual classes on students’ academic performance in Ilorin metropolis of Kwara state. The study used descriptive survey method. The population of the study comprised all the 367 academic staff of the selected secondary schools in Ilorin metropolis where 122 SSS3 teachers were purposively selected. Questionnaire and proforma were used to garner the needed data, where the questionnaire was validated and reliability coefficient of 0.71 was stablished using the split-half method. The study revealed amongst others poor or no autonomous/compulsory reading, difficulty in supervision, copying among the students, power/battery issues, absence online, and technical issues. The study then recommended amongst others that school administrators, government and all stakeholders in education should help to reduce digital divide and that students should learn with the growing or evolving technology.